Standing second sound wave in many-layer systems - Nemchenko, K.; Rogova, S. (Физика низких температур, 2012)
The variation of thermodynamic parameters of superfluid helium in standing second sound wave is studied.
Such double-layer systems as heater–helium and helium–detector are considered. Heat transfer in the heater and
the detector was described with usual thermal conductivity equation. Temperature and heat transfer in superfluid
⁴He was described with the system of equations for superfluid with taking into accounts both dissipative thermal
conductivity mode and second sound mode. Resonance frequency and amplitude dependence on dissipation at
the heater and the detector was studied. The unusual resonance was found in the double-layer system helium–
detector.